2018
DOI: 10.1007/s13770-018-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Click Chemistry-Based Injectable Hydrogels and Bioprinting Inks for Tissue Engineering Applications

Abstract: BACKGROUND: The tissue engineering and regenerative medicine approach require biomaterials which are biocompatible, easily reproducible in less time, biodegradable and should be able to generate complex three-dimensional (3D) structures to mimic the native tissue structures. Click chemistry offers the much-needed multifunctional hydrogel materials which are interesting biomaterials for the tissue engineering and bioprinting inks applications owing to their excellent ability to form hydrogels with printability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 131 publications
1
87
0
Order By: Relevance
“…374 Over the past two decades, copper-based ''click'' chemistry reactions have been a common strategy for synthesizing hydrogels. 375 In addition, bioorthogonal ''click'' chemistry is used to describe the way of generating products by joining small biomolecules such as proteins that occur in the presence of macromolecules such as proteins or cells. 375 Bio-orthogonal ''click'' chemistry is recognized as a promising molecular labeling approach, which does not affect normal biochemical processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…374 Over the past two decades, copper-based ''click'' chemistry reactions have been a common strategy for synthesizing hydrogels. 375 In addition, bioorthogonal ''click'' chemistry is used to describe the way of generating products by joining small biomolecules such as proteins that occur in the presence of macromolecules such as proteins or cells. 375 Bio-orthogonal ''click'' chemistry is recognized as a promising molecular labeling approach, which does not affect normal biochemical processes.…”
mentioning
confidence: 99%
“…375 In addition, bioorthogonal ''click'' chemistry is used to describe the way of generating products by joining small biomolecules such as proteins that occur in the presence of macromolecules such as proteins or cells. 375 Bio-orthogonal ''click'' chemistry is recognized as a promising molecular labeling approach, which does not affect normal biochemical processes. 376 Using these approaches, researchers can synthesize novel polymers and multifunctional hydrogels for biomedical applications.…”
mentioning
confidence: 99%
“…It was recently shown that the biorthogonal Diels-Alder click reaction between tetrazine (Tet) and transcyclooctene (TCO) can proceed rapidly under physiological conditions even in the absence of an external catalyst [28][29][30][31][32] . To our knowledge, there are very few published studies on the use of injectable click-cross-linked HA hydrogels in cartilage tissue engineering of hPLSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic hydrogels, as a new class of modern materials, have received significant attention recently . The simultaneous presence of incompatible hydrophilic and hydrophobic parts has endowed unique and interesting properties to these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic hydrogels, as a new class of modern materials, have received significant attention recently. [1][2][3][4][5] The simultaneous presence of incompatible hydrophilic and hydrophobic parts has endowed unique and interesting properties to these materials. For example, due to the presence of the hydrophobic units, amphiphilic hydrogels have improved mechanical properties compared with homopolymer hydrophilic hydrogels.…”
Section: Introductionmentioning
confidence: 99%